Under pressure: deep-sea elasmobranchs experience high mortality and stress in a crustacean trawling fishery - Graça Aranha, Sofia; Teodósio, Alexandra; Marsili, Tiago; Pires da Rocha, Pedro; Modesto, Teresa; Guerreiro, Pedro M.; Tambutte, Aurélien; Alves, Alexandra; Relvas, Paulo; Dias, Ester (Frontiers in Fish Science, 2025)
Crustacean bottom trawling in southern Portugal is an economic and culturally important fishing activity but may result in considerable bycatch of deep-sea elasmobranchs (DSE). Due to DSE life-history strategies, at-vessel mortality (AVM) rates in crustacean bottom trawl fisheries are expectedly high but require further investigations. This study assessed the at-vessel condition of 18 species of DSE, and AVM rates and stress of four deep-sea shark species (Etmopterus pusillus, E. spinax, Galeus melastomus, and Scymnodon ringens), to understand the impact of bottom trawling on these animals. Opportunistic sampling on a crustacean trawler in the southern Portuguese coast, revealed that 95% of specimens were either dead (n = 1,258) or in poor condition (n = 224) upon collection, underscoring their minimal chance of post-release survival. General linear model analyses showed that AVM was species-specific and highest in smaller sharks, as well as in those from hauls that exhibited larger temperature differences between bottom and surface waters, and those caught in hauls with heavier codend weight using a 55 mm codend mesh (targeting shrimp and prawns) instead of those caught in hauls using a 70 mm codend mesh (targeting Norway lobster). Stress, evaluated through metabolites and electrolytes levels in sharks' plasma, indicated significant differences in potassium, urea, and magnesium levels between live and deceased specimens of E. pusillus and G. melastomus, suggesting these as reliable mortality markers. Elevated lactate levels in G. melastomus further pointed to high post-release mortality risk. These findings highlight an urgent need to find solutions to mitigate the impacts of bottom trawling on those DSE, which are thoroughly discussed. A coordinated, multi-stakeholder approach involving researchers, the fishing industry, and regulatory bodies is crucial for developing and implementing effective, and more sustainable fisheries management and protection of DSE populations.